2019
DOI: 10.18196/ijief.128
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of E-Banking Acceptance in Oman: The Case of Islamic Banks’ Customers

Abstract: The main objective of this study is to examine the factors that influence the customers' intention to adopt E-banking services in Oman across the Islamic Banking sector. This research endeavours to assess the willingness of the Islamic banks' customers to adopt these services rather than the traditional banking methods. Accordingly, a sample of 300 Islamic banks' customers were surveyed in different districts of Oman. Afterwards, linear regression and one sample t-test were utilized in order to analyse the gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Inconsistency and insufficiency about these services both from the bank and the website of these applications can be a severe obstacle in its adoption, decreasing the satisfaction of even already informed customers (Laforet & Li, 2005;Poon, 2008). It is worth noting that expert advice, special training seminars, and government interventions are proven to increase customers' satisfaction, facilitate information, and promote the use (Wan et al, 2005;Echchabi et al, 2019). Some personal features of individuals, including the perception that the use of such services, would enhance people's prestige and elements of user's culture confirmed to impact the adoption (Al-smadi, 2012;Boateng et al, 2016;Huang, 2018;Tam & Oliviera, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Inconsistency and insufficiency about these services both from the bank and the website of these applications can be a severe obstacle in its adoption, decreasing the satisfaction of even already informed customers (Laforet & Li, 2005;Poon, 2008). It is worth noting that expert advice, special training seminars, and government interventions are proven to increase customers' satisfaction, facilitate information, and promote the use (Wan et al, 2005;Echchabi et al, 2019). Some personal features of individuals, including the perception that the use of such services, would enhance people's prestige and elements of user's culture confirmed to impact the adoption (Al-smadi, 2012;Boateng et al, 2016;Huang, 2018;Tam & Oliviera, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The impact of technology acceptance factors, such as the perceived usefulness and ease of use of these applications is also significant. Both perceived usefulness, including saving money and time using these applications combined with a 24-hour service (Akinci et al, 2004;Daneshgadesh & Yildirim 2014;Ege & Tatar, 2017;Ajimon, 2018;Uddin et al, 2018), as well as the perceived ease of use of these services can lead directly and indirectly to their adoption (Chau & Ngai 2010;Al-smadi, 2012;Mwiya et al, 2017;Wan et al, 2005;Agrawal et al, 2017;Echchabi et al, 2019). A practical, simple, and straightforward operating application enhances the satisfaction of even already users, increasing its perceived value and establishing a positive attitude towards these services, leading to maintenance of the use (Altobishi et al, 2018;Nkyoi et al, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Moreover, the rapid changes in internet technology also take part in making complications for e-banking (Aladwani, 2001a). The interlock between the change in technology, technology acceptance dynamics in terms of public at large, and associated challenges make it a tedious task that ranges from strategic alignment to tactical complexities (Echchabi et al, 2019;Koenaite et al, 2019;Nui Polatoglu & Ekin, 2001;Pikkarainen et al, 2004;Rahi et al, 2019;Ramesh et al, 2019;Siyal et al, 2019;Wang et al, 2003).…”
Section: Technology Acceptance (Eb-i4)mentioning
confidence: 99%
“… The comparison between the developed, developing and underdeveloped countries is also a missing link (Malaquias & Hwang, 2019).  The Islamic banking sector can be the focus of the future studies, even though, the banks selected have Islamic banking branches and some specialize in Islamic banking operations (Bidabad & Allahyarifard, 2019;Echchabi et al, 2019;Mohd Thas Thaker et al, 2019;Raza & Hanif, 2011). …”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…For example, a study conducted in Kuwait by Aladwani (2001) showed that customers perceived a number of potential internet banking challenges including consumer privacy, legal regulation, security, bank reputation, and bank trustworthiness. Another study was conducted in the Omani market by Echchabi, Al-Hajri, and Tanas (2019): they studied the factors that affect the acceptance of online banking services by Islamic bank customers in Oman. The results showed that selfefficacy, ease of use, relative advantage, and facilitating conditions were the main determinants of online banking acceptance.…”
Section: Research On Internet Banking Adoptionmentioning
confidence: 99%